2014
DOI: 10.1111/2049-632x.12134
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm models for the food industry: hot spots for plasmid transfer?

Abstract: Biofilms represent a substantial problem in the food industry, with food spoilage, equipment failure, and public health aspects to consider. Besides, biofilms may be a hot spot for plasmid transfer, by which antibiotic resistance can be disseminated to potential foodborne pathogens. This study investigated biomass and plasmid transfer in dual-species (Pseudomonas putida and Escherichia coli) biofilm models relevant to the food industry. Two different configurations (flow-through and drip-flow) and two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…This provides the biofilm with what has been termed the “insurance hypothesis” in ecology that considers that the stability of many biological communities relies on their diversity which increases the chance that some members will be able to withstand environmental variations that the community may encounter (Boles et al, 2004). This enhanced clonal diversity in biofilms is a real challenge in the control of pathogen and detrimental biofilms as they may rapidly adapt to environmental stresses such as treatments with antimicrobials (Macià et al, 2011; Koch et al, 2014; Van Meervenne et al, 2014). In contrast, this diversity is a real benefit in biotechnological issues in which biofilms can be exploited in numerous applications and under many different environmental conditions (Berlanga and Guerrero, 2016; Piard and Briandet, 2016).…”
Section: Microbial Systems To Shape Biofilm Structurementioning
confidence: 99%
“…This provides the biofilm with what has been termed the “insurance hypothesis” in ecology that considers that the stability of many biological communities relies on their diversity which increases the chance that some members will be able to withstand environmental variations that the community may encounter (Boles et al, 2004). This enhanced clonal diversity in biofilms is a real challenge in the control of pathogen and detrimental biofilms as they may rapidly adapt to environmental stresses such as treatments with antimicrobials (Macià et al, 2011; Koch et al, 2014; Van Meervenne et al, 2014). In contrast, this diversity is a real benefit in biotechnological issues in which biofilms can be exploited in numerous applications and under many different environmental conditions (Berlanga and Guerrero, 2016; Piard and Briandet, 2016).…”
Section: Microbial Systems To Shape Biofilm Structurementioning
confidence: 99%
“…The genotypes of mixed‐species biofilms are difficult to reconcile. Several studies have suggested that mixed‐species biofilms enhance EPS production (Jahid and others 2014), eDNA formation (Pammi and others ), internalization to foods (Jahid and others 2014), higher heterogeneity of the populations, competitive interactions (Guillier and others ), composition and spatial organization of species, that is, resilience (Lee and others ), and horizontal gene transfer (Aminov ) including conjugal plasmid transfer (Reisner and others ; Meervenne and others ). Another report documents that the luxS (AI‐2) mutant strain of Streptococcus gordonii is able to form a mixed‐species biofilms with the wild‐type Porphyromonas gingivalis strain but not with the AI‐2 mutant strain, suggesting the cooperative usage of AI‐2 molecules by both species (McNab and others ).…”
Section: Paradox Of Fitness Of Different Populations In Mixed‐speciesmentioning
confidence: 99%
“…Spatial structuring is important for species composition 22 and can promote horizontal gene transfer by sustaining high bacterial density and metabolic activity, and increasing physical proximity of bacterial cells 2325 . Heightened conjugative plasmid transfer in biofilms has been shown in one- and two-species systems 26,27 , but not in more complex multispecies communities. Moreover, experimental demonstration linking community level effects of sub-MICs, spatial structuring, and horizontal transfer of antibiotic resistance genes is completely lacking.…”
Section: Introductionmentioning
confidence: 99%